Mental Health Experiences of Female Adolescent Santri Following Islamic Coaching with the I.S.L.A.M Model: A Qualitative Study in an Indonesian Pesantren - Aisyah Muhammad Ikhwan; Yudistira Fauzi Indrawan (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
This study examines the perceived mental health experiences of female adolescent santri after participating in Islamic Coaching with the I.S.L.A.M Model in an Indonesian pesantren. Adolescent mental health remains a serious concern in Indonesia, including among santri who live within structured religious, academic, and residential environments. Although coaching has been used as a non-clinical form of support, limited qualitative research has examined how spiritually grounded coaching is experienced by adolescent santri in Islamic boarding school settings. This study used an exploratory qualitative design with a phenomenological orientation. Five female santri aged 14 to 17 years who had completed Islamic Coaching sessions using the I.S.L.A.M Model were selected through purposive sampling, and one additional informant was included to provide contextual information. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis. The findings show that participants perceived the coaching process as a relatively safe and structured space for emotional expression, self-reflection, social boundary-setting, and spiritual coping. Their narratives reflected interconnected emotional, psychological, social, moral, and spiritual dimensions of mental health. The elements of Intention, See, Learn, Action, and Munajat were perceived as helpful because they supported participants in clarifying feelings, reinterpreting personal difficulties, recognizing personal capacity, taking practical steps, and reconnecting emotional experiences with prayer and reliance on Allah. This study contributes to the discussion of adolescent mental health in pesantren by offering a contextual account of Islamic Coaching as a non-clinical, spiritually grounded form of support. The findings should be read as participants’ perceived experiences rather than evidence of clinical effectiveness.